Caregiver-reported physical health status of children and young people with fetal alcohol spectrum disorder. (9th June 2021) - Reid, N.; Hayes, N.; Young, S. B.; Akison, L. K.; Moritz, K. M.
Abstract: While fetal alcohol spectrum disorder (FASD) has primarily been thought of as a neurodevelopmental condition, research is beginning to highlight its 'whole-body' implications. Accordingly, the current study sought to provide a snapshot of potential health issues. Caregivers of children (median age of 12 years) with an FASD diagnosis were invited to participate in an online survey. Information relating to sample demographics, FASD status of the child and health outcomes were collected. The prevalence of health conditions reported in the FASD sample was compared against national prevalence data. Multiple linear regression utilising a stepwise approach was used to investigate potential predictors of the number of diagnosed health conditions. Survey data were from an international cohort ( n = 197), with the majority of respondents based in Australia (40.2%) or the United States (27.7%). The most commonly reported diagnosed health conditions were eye conditions (44.7%), asthma (34.5%), heart conditions (34.0%) and skin conditions (27.4%). Binomial testing indicated the proportion of children diagnosed with these disorders was generally higher in the current FASD population, compared to national prevalence data. Indicators of metabolic dysfunction including diabetes and obesity were not significantly different compared to national prevalence data. Age of FASD diagnosis, existence of comorbid mental health conditions and the primary caregiver being in paid work were identified as being associated with the prevalence of diagnosed health conditions. Overall, the study has provided an up-to-date snapshot of health problems reported in a sample of children with FASD, confirming their increased risk of adverse health outcomes.